Christian Cinema as Part of Pastoral Theology. Challenges in the Context of Artificial Intelligence Applications - Klauza, Karol (Roczniki Nauk Społecznych, 2024)
From the birth of the cinema, the pastoral communication of the Church received a new and effective aid to religious formation. Today, the use of digital technology in the production of new film genres is increasing and artificial intelligence is influencing human consciousness and choices, as suggested by the work of directors and screenwriters. This challenges Christian identity and requires deep learning in moral axiology and religious formation on the part of producers, artificial intelligence algorithm developers and even viewers. In order to analyse the ethical and moral value of cinematic communication using artificial intelligence (e.g. chat, images, art), the Catholic Church, in collaboration with Judaism and Islam, announced on January 13th, 2023 the ‘Roman Call’ on the ethical use of artificial intelligence. The document formulates the principles of transparency, inclusion, responsibility, impartiality, reliability, security and privacy.